Self-Regulated Learning (IntechOpen, 2025)
Self-Regulated Learning - Insights and Innovations explores the multifaceted nature of self-regulated learning (SRL) in today's dynamic educational landscape. This book serves as both a reflection on current SRL practices and a roadmap for future advancements. It offers a comprehensive look at SRL across diverse educational settings, examining topics from the application of AI in predicting educational outcomes to integrating digital tools for self-directed learning in pre-service teachers. Readers will discover the latest research, theoretical insights, and actionable strategies applicable to various learning environments. The book investigates the foundational theories of SRL, including its pivotal role in developing cognitive and metacognitive skills, and explores effective strategies for supporting learners, such as deep notetaking for underserved communities. Finally, it addresses future directions for SRL, showcasing examples of learners thriving through self-regulation. This volume is a valuable resource for educators, academic coaches, and policymakers seeking to understand and foster SRL in learners, empowering them to adapt, persist, and excel.